Strategi Penghimpunan Dan Pendistribusian ZISWAF Dalam Penanganan Covid 19 Di BAZNAS Banjarnegara - Nurhidayah, Peni (Program Studi Hukum Ekonomi Syariah, 2022)
The global pandemic has had a negative impact, one of which is the people's economy which resulted in social inequality. Many people have been affected by the COVID-19 pandemic to help solve this problem. BAZNAS Banjarnegara provides several social programs so that a strategy for raising funds and distributing ZISWAF is carried out for handling Covid 19. The purpose of this research is to find out the strategy for collecting and distributing ZISWAF funds in handling Covid 19 in Indonesia. BAZNAS Banjarnegara. This field research uses qualitative methods with data collection techniques through observation, interviews, and documentation. The results showed that BAZNAS Banjarnegara during the covid 19 pandemic used a strategy of raising funds directly through a fund-picking program and indirectly through social media promotions and transfers. The strategy for distributing funds is channeled to communities affected by COVID-19 through the assistance of student data packages, basic food assistance for poor families, and medical expenses assistance given to families of zakat mustahik.